2007
DOI: 10.1055/s-2007-970925
|View full text |Cite
|
Sign up to set email alerts
|

Borderline-Persönlichkeitsstörung und Transsexualität

Abstract: The data obtained refute the often-assumed increased relationship between borderline personality disorders and transsexuality. It should be assumed that a borderline personality disorder is primarily a psychiatric illness, while transsexuality is a disorder of gender identity in which secondary borderline symptoms may arise in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
0
6
0
4
Order By: Relevance
“…High percentages of psychiatric comorbidity, however, are not always found. In many studies, transsexuals were found to generally function well psychologically in the nonclinical range (e.g., Cole, O'Boyle, Emory, & Meyer, 1997;Gómez-Gil, Trilla, Salamero, Godás, & Valdés, 2009;Haraldsen & Dahl, 2000;Mate-Kole, Freschi, & Robin, 1990;Miach, Berah, Butcher, & Rouse, 2000;Seikowski, Gollek, Harth, & Reinhardt, 2008;Smith, van Goozen, & CohenKettenis, 2001;Smith et al, 2005). Indeed, clinically, one may see applicants who are employed, have relationships, and function socially without any problems, yet very strongly desire sex reassignment.…”
Section: The Necessity Of the D Criterion For A Gid Diagnosismentioning
confidence: 99%
“…High percentages of psychiatric comorbidity, however, are not always found. In many studies, transsexuals were found to generally function well psychologically in the nonclinical range (e.g., Cole, O'Boyle, Emory, & Meyer, 1997;Gómez-Gil, Trilla, Salamero, Godás, & Valdés, 2009;Haraldsen & Dahl, 2000;Mate-Kole, Freschi, & Robin, 1990;Miach, Berah, Butcher, & Rouse, 2000;Seikowski, Gollek, Harth, & Reinhardt, 2008;Smith, van Goozen, & CohenKettenis, 2001;Smith et al, 2005). Indeed, clinically, one may see applicants who are employed, have relationships, and function socially without any problems, yet very strongly desire sex reassignment.…”
Section: The Necessity Of the D Criterion For A Gid Diagnosismentioning
confidence: 99%
“…For example, Madeddu, Prunas, and Hartmann [33] identified no case of BPD using the Structured Clinical Interview for DSM-IV (SCID) in a sample of 16 female-to-male transsexuals (see also Lobato et al [34]). Although other studies have identified modest elevations of BPD traits among female-to-male transsexuals [35,36], there is little indication that the association is specific to GID because many of these studies failed to include clinical control comparison groups. In the present study, starting with a sample of BPD women, there was clearly no evidence at all for GID caseness.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the sexologists did not refer to aetiology at all (e. g. Clement/Senf 1996;Gauruder-Burmester/Popken/Beier 2006;Seikowski 2007), since hypotheses on biological causes have so far been either falsified or proven unverifiable, and psychosocial causes have turned out not to be generalisable (Bosinski 2000: 72;Rauchfleisch 2006: 20). Second, the debate in sexology from the 1990s to 2010 placed more emphasis on pragmatic issues, such as aspects related to the overall concept of treatment (e. g. Clement/Senf 1996;Kockott 1996;Becker et al 1997; Beier/Bosinski/Loewit 2005; Gauruder-Burmester/Popken /Beier 2006;Sigusch 1996;, specific aspects in psychotherapy (e. g. Meyenburg 1992;Bosinski 1994;Laszig/Knauss/Clement 1995;Clement/Senf 1996a;Pfäfflin 1996;Eicher 1996;Rauchfleisch 2006;Seikowski 2007;Seikowski et al 2008) and on conceptual aspects, such as the issue of depathologisation (Sigusch 1991;1991a;1995a;Hirschauer 1992;Lindemann 1992;Augstein 1992;Langer 1995). 3 | For a comprehensive discussion of somatic approaches to transsexuality in Western countries, see Nieder/Jordan/Richter-Appelt 2011).…”
Section: Critical Approachmentioning
confidence: 99%
“…While pathologising concepts generally classified transsexuality as a ›gender identity disorder‹, sexologists in Germany, unlike their U.S. colleagues, clung to the term ›transsexuality‹ or variations of the term. Moreover, despite the fact that the majority of sexologists employed the terms ›transsexuality‹ (e. g. Sigusch 1991a;Clement/Senf 1996;Becker et al 1997;Seikowski 2007;Seikowski et al 2008) or ›transsexualism‹ (e. g. Langer 1995), the meanings were not necessarily identical.…”
Section: Terminolog Y Definitions and Concepts From The 1990s To 2010mentioning
confidence: 99%